Genetic Impact on Bone Modulation—A Review Bridging Bioscience to Genetic Engineering - CK, Anulekha Avinash; Tholupunuri, Harshini; Reddy, M. Ramu; Muralidhar, Mamatha; Jayyarapu, Dilip; Nair, Sangeeta (Global Medical Genetics, 2021)
Genes control approximately 60% to 75% of the variance of peak bone mass/density and a much smaller amount of variance in rate of loss.Bone mass increases during growth to a peak value and soon after begins to decline. Most of the genetic effect is exerted during growth and so influences peak bone mass; whether there is an additional genetic effect on the rate of bone loss is less clear. So, this article aims to place emphasis on various oral and systemic conditions that are manifested due to altered gene function. Genetic polymorphisms and mutations are simple, although the consequences of the mechanism are complex. The syndromic manifestation due to changes at genetic level will greatly affect the bone quality, which will ultimately affect any treatment prognosis. Hence, a better understanding of molecular mechanisms of bone remodeling helps to identify pathogenic causes of bone, skeletal diseases, and leads to the development of targeted therapies for these diseases. This review highlights notions on the connecting link between science and genetics as well as various oral scenarios where gene could bring about changes, resulting in deformities. There is an intense research awaited in the future which could intervene with the causes that bring about genetic modulations, so as to decrease the mortality rate of humans.
Keywords: Keywords; genetic mutations syndromes bone resorption